Transfusion Medicine Competency And The Fundaments For Its Implementation In Anesthesiology And Reanimation - Frenandez Franch, Neyda; Torres Romo, Ubaldo Roberto; Menéndez Cabezas, Arturo Teodoro; López Lazo, Sarah Estrella; Fuentes Díaz, Zaily; Liza Hernández, Oscar (Revista Cubana de Investigaciones Biomédicas, 2019)
A way to overcome the blood transfusion disadvantages is determining and developing transfusion competencies. The research aims were to identify the elements of transfusion medicine competency and to describe the fundaments for its implementation in the specialty of Anesthesiology and Reanimation. Transfusion competencies include, among others, knowledge of the risks of blood-borne infections, safe prescription of blood products, identification of transfusion reactions, and competently perform and teach undergraduates the procedure of intravenous infusion of blood and blood products. It also includes knowing and updating on ethical, scientific and legal issues of blood components transfusion. In Anesthesiology and Reanimation, transfusion medicine competency also involves demonstration of knowledge, abilities and values for the preoperative preparation of the patients with anemia, bleeding risk and other hematological illnesses, for the use of pharmacological and non pharmacological alternatives, as well as for blood components’ economy. Being competent in transfusion medicine in this specialty implies an important and substantial reduction of the general morbidity-mortality and particularly that associated with transfusion complications, and requires the capacity of mobilize the set of knowledge, skills, attitudes and values in a comprehensive and pertinent way in order to transfuse less and better, with more safety and less expenditures.